Simple method for making MWCNTs/Au-NPs-based biosensor electrodes. (28th January 2022) - Subagio, Agus; Taufiq, Heydar Ruffa; Khumaeni, Ali; Umiati, Ngurah Ayu Ketut; Adi, Kusworo
Abstract: Multiwalled carbon nanotubes have great potential when applied as biosensors. Their properties, especially as electrodes with electrochemical characteristics, offer strong benefits for developing biosensors. This research has been able to integrate multiwalled carbon nanotubes (MWCNTs) with Au nanoparticles (Au-NPs) to obtain several new superior properties. Cysteaminium chloride is used to link MWCNTs and Au-NPs while binding to specific antibodies to make them more sensitive to some diseases or viruses. The data on the success of the bonding of MWCNTs/Au-NPs were tested using three characterizations, namely FTIR, SEM, and XRD. Based on the results of testing electrochemical properties using the CV and EIS tests, the capacitance value of 6, 363 Fg −1 and the Rct value of 717, 9 Ω, respectively. This demonstrates good adhesion and electron transfer properties from the electrolyte to the probe and electrode.